Design and implementation of an intelligent fuzzy logic controller (FLC) for Air Handling Unit (AHU) for smart house - Salami, Momoh Jimoh Emiyoka; Rashid, Muhammad Mahbubur; Mohammad, Noor (INSI Publications, 2011)
Intelligent Building Automation System (IBAS) is one of the heaviest researched areas motivated by the continuous high demand on economically-effective systems that are designed to provide a desirable controlled space for various organizations. IBAS has been developed along with the rapid sophistication of the information and control technologies in this study. The main objective of the continuous effort is to provide an intelligent monitor and control of various facilities within the building so as to offer its users or occupants with effective security, improved productivity, human comfort, and efficient energy management. Heat, Ventilation and Air Conditioning (HVAC), Lighting Systems, Life and Safety System, and Access Control are some of the typical systems that formed IBAS in most modern building. HVAC and Lighting systems constitute the major energy consumer in an entire building that focuses particularly on the improvement of monitor and control of these systems.